The Impact of Learning Oriented Assessment (LOA) on Student’s Speaking Anxiety - Arifin, Nurul; Fakhruddin, Zulfah; Zain, Nurhamdah; Yusuf, Muh (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This quasi-experimental study examined the impact of Learning Oriented Assessment (LOA) on students’ speaking anxiety in English as a Foreign Language (EFL) classrooms. The research involved fifth-semester students enrolled in the English Education Study Program at IAIN Parepare, divided into experimental and control groups. The experimental group received speaking instruction integrated with LOA practices including formative feedback, self-assessment, and peer evaluation, while the control group was taught using traditional assessment methods. Data were collected using a post-test questionnaire adapted from the EFL Public Speaking Class Anxiety Scale and analyzed through independent samples t-test. The findings revealed a statistically significant difference between groups, t(42) = −3.477, p = .001, with the experimental group exhibiting significantly lower speaking anxiety (M = 41.36, SD = 8.61) compared to the control group (M = 49.91, SD = 7.67). The effect size analysis demonstrated a large magnitude (Cohen’s d = −1.048), indicating both statistical and practical significance. Further analysis identified self-assessment as the most effective LOA component in reducing anxiety, followed by formative feedback and peer feedback. These results confirm that LOA effectively reduces speaking anxiety by creating a psychologically safe learning environment that emphasizes learning progress over summative judgment, thereby reducing fear of negative evaluation and performance pressure among EFL learners